Seaweed (Laminaria digitata) and Honey Kombucha: A Fermented Antioxidant-Rich Beverage - Anastasia Karpova; Deborah Adesina; Furong Tian; Azza Silotry Naik (Fermentation, 2025)
Kombucha is a sweetened tea infusion fermented using a symbiotic culture of bacteria and yeast (SCOBY). Recently, kombucha has gained popularity due to its potential health benefits, attributed to its high antioxidant and probiotic properties. The aim of this research was to formulate a novel antioxidant-rich beverage with symbiotic benefits by utilizing ingredients such as Laminaria digitata (brown seaweed), cinnamon, and lavender adjuncts, alongside alternative substrates like acacia honey and conventionally used ingredients such as ginger (Zingiber officinale Roscoe). This study comprehensively evaluated parameters including pH levels, acidity, alcohol content, color, and antioxidant potential of the beverages. All kombucha beverages exhibited significantly high antioxidant potential levels, particularly in Honey Kombucha (HK) samples, which ranged between 164.44 and 164.78% 2,2-Diphenyl-1-picrylhydrazyl (DPPH) inhibition, and 155.44–155.29 µg Trolox Equivalent (TE)/mL for the Ferric-reducing antioxidant power (FRAP) assay on days 3 and 7. Sugar Kombucha Seaweed (SKS) and Sugar Kombucha Cinnamon (SKC) samples received the highest acceptability for flavor from the sensory panel, with scores of 87.5% and 70%, respectively. However, Honey Kombucha Ginger (HKG) received the lowest acceptability with only 12.5%. The added adjuncts and substrates significantly influenced the antioxidant potential compared to plain unfermented tea (PT). This research paper outlines well-characterized fermentation process for formulating health-promoting beverages utilizing locally sourced ingredients.